Perancangan Logo UMKM untuk Branding sebagai Identitas Baru - Rahmawati, Ayu; Nurul Husna, Ade Irvi (LPPM Universitas Bina Sarana Informatika, 2023)
Branding in UMKM can increase the level of sales in the market, and branding also has advantages, because in the Indonesian economic sector which is growing rapidly in the business world, namely UMKM. As in packaging, there are mixed logos, names, terms, or designs that are determined or intended to be used in branding in creating a new identity. In RT 05 Cihanjawar Village, it turns out that there are no UMKM yet, so students are helped to develop UMKM and one of them is by making a logo for branding as a new identity that there is Kicimpring UMKM in RT 05. The method used is an approach to residents who will open UMKM to make a logo as a branding for the marketing process. Besides that, it also explains the importance of a logo for a product. So that the result of his dedication is the formation of a logo for Kicimpring UMKM that is in accordance with the request of the business owner.